Perceptions and acceptability of an experimental Ebola vaccine among health care workers, frontline staff, and the general public during the 2014–2015 Ebola outbreak in Sierra Leone. Issue 11 (7th March 2019) - Jalloh, Mohamed F.; Jalloh, Mohammad B.; Albert, Alison; Wolff, Brent; Callis, Amy; Ramakrishnan, Aparna; Cramer, Emily; Sengeh, Paul; Pratt, Samuel Abu; Conteh, Lansana; Hajjeh, Rana; Bunnell, Rebecca; et al.
Abstract: Introduction: Experimental Ebola vaccines were introduced during the 2014–2015 Ebola outbreak in West Africa. Planning for the Sierra Leone Trial to Introduce a Vaccine against Ebola (STRIVE) was underway in late 2014. We examined hypothetical acceptability and perceptions of experimental Ebola vaccines among health care workers (HCWs), frontline workers, and the general public to guide ethical communication of risks and benefits of any experimental Ebola vaccine. Methods: Between December 2014 and January 2015, we conducted in-depth interviews with public health leaders (N = 31), focus groups with HCWs and frontline workers (N = 20), and focus groups with members of the general public (N = 15) in Western Area Urban, Western Area Rural, Port Loko, Bombali, and Tonkolili districts. Themes were identified using qualitative content analysis. Results: Across all participant groups, not knowing the immediate and long-term effects of an experimental Ebola vaccine was the most serious concern. Some respondents feared that experimental vaccines may cause Ebola, lead to death, or result in other adverse events. Among HCWs, not knowing the level of protection provided by experimental Ebola vaccines was another concern. HCWs and frontline workers were motivated to help find a vaccine for Ebola to help end the outbreak. General public participants cited positive experiences with routine childhood immunization in Sierra Leone. Discussion: Our formative assessment prior to STRIVE's implementation in Sierra Leone helped identify concerns, motivations, and information gaps among potential participants of an experimental Ebola vaccine trial, at the time when an unprecedented outbreak was occurring in the country. The findings from this assessment were incorporated early in the process to guide ethical communication of risks and benefits when discussing informed consent for possible participation in the vaccine trial that was launched later in 2015.